Fatigue behavior and strength evaluation of vertical stiffener welded joint in orthotropic steel decks. (December 2016) - Yang, Muye; Ji, Bohai; YuanZhou, Zhiyuan; Fu, Zhongqiu
Abstract: This study focuses on the fatigue strength and crack behaviors at weld toe of vertical stiffener and deck in orthotropic steel decks. A total of 20 specimens have been carried out in fatigue tests in relation to the two types of welded joints and diverse stress conditions. The crack initiation and propagation behaviors were comparative analyzed based on four stages of cracking process. In addition, the geometry properties of welded joints were measured in cross sections, and their effect on stress concentration factors was investigated by test and FE analysis. Based on these, the stress concentration factors were calculated and compared by hot spot stress method. Finally, the fatigue strength of this structural detail had been investigated by comparing the fatigue test results and the corresponding regression SN curves. Fatigue strength of partial penetration welded joint is slightly larger than full penetration welded joint before toe crack initiation. However, based on the crack behaviors in the propagation process on the whole, it is acceptable to evaluate these two kinds of welded joint by the same SN curve in practical engineering application.Using the same SN curve JSSC-G (50 MPa) for the allowable fatigue strength evaluation of this structural detail in China was recommended. Highlights: Fatigue tests were carried out to investigate the fatigue strength of welded joint between vertical stiffness and deck plate The crack initiation and propagation behaviors were comparative analyzed based on four cracking stages The effect of geometry properties of two types welded joints on stress concentration were investigated The fatigue strength of this structural detail was evaluated and recommended in relation to the diverse stress conditions